HUBUNGAN MINAT BACA DENGAN KETERAMPILAN MENULIS BERITA SISWA KELAS VIII SMP NEGERI 24 PADANG - Satini, Ria; Hayati, Najmi (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2019)
This study aims to describe the relationship of reading interest with news writing skills of class VIII SMP 24 Padang. The population in this study were class VIII students of SMP 24 Padang as many as 252 students. The sample in this study amounted to 40 students whose sampling was done by proportional random sampling. Data collection is done through questionnaires and performance tests. Questionnaire is used to determine the level of mastery of students' reading interest, performance tests are conducted to find out the results of news writing skills. Data analysis and discussion were carried out descriptively correlational. Based on the results of data analysis obtained the following research findings. First, the level of mastery of reading interest in class VIII students of SMP Negeri 24 Padang is quite adequate, which is equal to 67.85. Second, the level of mastery of news writing skills of class VIII students of SMP Negeri 24 Padang is quite sufficient, which is 73.5. Third, the correlation coefficient of reading interest with news writing skills is quite sufficient at 0.448.